2017
DOI: 10.1038/s41598-017-17228-x
|View full text |Cite
|
Sign up to set email alerts
|

Workflow assessing the effect of gait alterations on stresses in the medial tibial cartilage - combined musculoskeletal modelling and finite element analysis

Abstract: Knee osteoarthritis (KOA) is most common in the medial tibial compartment. We present a novel method to study the effect of gait modifications and lateral wedge insoles (LWIs) on the stresses in the medial tibial cartilage by combining musculoskeletal (MS) modelling with finite element (FE) analysis. Subject’s gait was recorded in a gait laboratory, walking normally, with 5° and 10° LWIs, toes inward (‘Toe in’), and toes outward (‘Toe out wide’). A full lower extremity MRI and a detailed knee MRI were taken. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(69 citation statements)
references
References 92 publications
10
59
0
Order By: Relevance
“…To assess changes in cartilage loading, finite element modeling and imaging of the knee joint using magnetic resonance imagine (MRI) is required 42 . A recent case study using subject-specific modeling and investigating effects of gait modifications found that changes in KAM were not correlated with changes in the medial contact pressures 43 . Devices, that can replicate the knee joint movement in vitro, such as that designed by van de Bunt et al (2017) 44 may also provide valuable insight into the effects of gait modifications on the cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…To assess changes in cartilage loading, finite element modeling and imaging of the knee joint using magnetic resonance imagine (MRI) is required 42 . A recent case study using subject-specific modeling and investigating effects of gait modifications found that changes in KAM were not correlated with changes in the medial contact pressures 43 . Devices, that can replicate the knee joint movement in vitro, such as that designed by van de Bunt et al (2017) 44 may also provide valuable insight into the effects of gait modifications on the cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…The state-of-the-art studies have introduced multiscale musculoskeletal finite element (MSFE) approaches using either sequential or embedded (concurrent) MS and FE models. In a sequential approach, a MS model is used to estimate joint kinematics, external joint moments, muscle forces, and consequently the JCF to drive a FE model [2], [14], [15]. Since the MS and the FE models are in series, highly complicated material models such as fibril-reinforced hyperelastic [14] or fibril-reinforced poroviscoelastic (FRPVE) [2], [15] materials can be employed to model the joint's soft tissues including cartilage and menisci.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, a major limitation of the sequential approach is that the MS estimations are independent of the FE model calculations i.e. soft tissue deformations [2], [14], [15]. In other words, the soft tissue deformation estimated by the FE model could alter the secondary kinematics.…”
Section: Introductionmentioning
confidence: 99%
“…Models based on medical images are the current gold standard, they provide the most accurate geometrical parameters (Scheys et al 2006;Blemker et al 2007;Valente et al 2014). In such methods, data from MRI (Kainz et al 2016(Kainz et al , 2017Halonen et al 2017), EOS V R (Cl ement et al 2015), or CT-scans (Bartels et al 2015;Marra et al 2015) was used to reconstruct 3D bone geometries through image segmentation manually (Valente et al 2014) or semi-automatically (Scheys et al 2005). Generally, imagery data acquisition and post-processing is time-consuming.…”
Section: Introductionmentioning
confidence: 99%